Modeling and study of dynamics of micro- beam coupled to two Josephson junctions - MONWANOU, VINCENT ADJIMON; CHABI OROU, JEAN BIO (My University, 2020)
In this work, we proposed to study the dynamics of a bi-recessed micro-beam coupled magnetically to two Josephson junctions. After building a model of micro electro mechanical systems (MEMS), the equations of their dynamics are determined. The fixed points of system are analytically checked and their stability is analyzed by using the Routh–Hurwitz criterion. For this purpose, a numerical study utilizing the bifurcation diagram, Lyapunov exponents, phase portraits and time histories is made to analyze the different dyanamic modes of micro-beam coupled to two Josephson junctions. The effect of Josephson junctions on the behavior of the micro-beam is seriously analyzed. It is obtained for each part of the MEMS the various dynamics influenced by certain parameters of the system.
Keywords: micro-beam; Josephson junctions; bifurcation; chaos; limit cycles